Gender Effects As Macro-Level Effects: Germany and the United States 1991-1997 - Lisa M. Amoroso (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
My research examines within-nation differences as well as cross-national differences in socially stratified outcomes, specifically the distribution of household incomes. I build on the considerable empirical evidence suggesting that group memberships are important factors in shaping one' s life course and in determining the level of social inequality. I examine seven years of longitudinal data from Germany and the United States, 1991-1997 to demonstrate that gender issituated within other salient social categories such as race and marital status. These qualitative distinctions form status-based groups that organize the social hierarchy in which individual action is both enabled and constrained.
Keywords: 330; Haushaltseinkommen; Familie; Frauen; Sozialer Status; Aggregation; Vergleich; Deutschland; USA; Soziale Gruppe